Role of Pediatricians, Pediatric Associations, and Academic Departments in Ensuring Optimal Early Childhood Development Globally: Position Paper of the International Pediatric Association. Issue 8 (16th October 2022) - Uchitel, Julie; Alden, Errol; Bhutta, Zulfiqar A.; Cavallera, Vanessa; Lucas, Jane; Oberklaid, Frank; Patterson, Janna; Raghavan, Chemba; Richter, Linda; Rikard, Blaire; Russell, Robert Ross; Mikati, Mohamad A.
Abstract : This article has supplementary material on the web site: www.jdbp.org . ABSTRACT: Early childhood (birth–8 years), particularly the first 3 years, is the most critical time in development because of the highly sensitive developing brain. Providing appropriate developmental care (i.e., nurturing care, as defined by the World Health Organization [WHO]) during early childhood is key to ensuring a child's holistic development. Pediatricians are expected to play a critical role in supporting early childhood development (ECD) through providing developmental services such as developmental monitoring, anticipatory guidance, screening, and referral to medical and/or community-based services when delay is identified. Pediatricians are also expected to serve as advocates within their clinics and communities for improved delivery of ECD services, such as advocating for increasing funding for ECD initiatives, increasing insurance coverage of ECD services, and working to increase other pediatricians' awareness of the principles of ECD and how to deliver developmental services. However, this does not always occur. Typically, pediatricians' training and practice emphasizes treating disease rather than enhancing ECD. Pediatricians are further hindered by a lack of uniformity across nations in guidelines for developmental monitoring and screening. In this article, we present the vision of the International Pediatric Association (IPA) of the roles that pediatricians, academic departments, medical training programs, and pediatric associations should fulfill to help support ECD, including raising ECD to higher levels of priority in routine pediatric care. First, we present the challenges that face these goals in supporting ECD. We then propose, with supportive literature, strategies and resources to overcome these challenges in collaboration with local and international stakeholders, including the IPA, the WHO, UNICEF, and the World Bank.